Monitoring of River Water Level Based on Internet of Things - Liambo, Wahyu Padliansyah; Sunardi, Sunardi (Signal and Image Processing Letters, 2023)
River water level monitoring is the process of monitoring water in rivers that sometimes overflow and cause flooding. Residents need to know the water level to serve as an early warning. Therefore, it is necessary to have a measurement mechanism and river water level information in order to provide information to the community. Monitoring river water levels in this research uses the HC-SR04 ultrasonic distance sensor and water level sensor. Arduino Uno is used as a microcontroller. This research uses a prototype with water level measurements observed at 3 cm (low), 3-5 cm (medium), and 5 cm (high). The water level can be monitored from anywhere through Blynk. The implementation of the resulting water level has been successful in accordance with the parameter values on the water level sensor which is marked by the display of numbers on the LED, the color of the lights, and different alarm sounds for each water level. HC-SR04 ultrasonic sensor is able to measure and provide water level data in realtime and from any place using Blynk.